2021
DOI: 10.3390/brainsci11030311
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Analysis of the Default Mode Network Using Resting-State fMRI in Down Syndrome: Relationships Highlighted by a Neuropsychological Assessment

Abstract: Background: Studies on complexity indicators in the field of functional connectivity derived from resting-state fMRI (rs-fMRI) in Down syndrome (DS) samples and their possible relationship with cognitive functioning variables are rare. We analyze how some complexity indicators estimated in the subareas that constitute the default mode network (DMN) might be predictors of the neuropsychological outcomes evaluating Intelligence Quotient (IQ) and cognitive performance in persons with DS. Methods: Twenty-two DS pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(42 reference statements)
2
4
0
Order By: Relevance
“…Resting-state functional MRI (rs-fMRI) showed altered default mode network (DMN) in our DS cohort (Fig. 7O), as previously reported ( 46 , 47 ).…”
Section: Resultssupporting
confidence: 88%
“…Resting-state functional MRI (rs-fMRI) showed altered default mode network (DMN) in our DS cohort (Fig. 7O), as previously reported ( 46 , 47 ).…”
Section: Resultssupporting
confidence: 88%
“…For instance, Hemmati et al (2013) studied EEG signals by means of fractal dimension in a sample of children with DS, and results indicated that patients with DS showed higher complexity values than controls. Such tendency was confirmed in fMRI studies focused on the estimation of complexity values in young adults ( Carbó-Carreté et al, 2020 ; Figueroa-Jimenez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 59%
“…Whether this could be due, at least in part, to an imbalance in the GnRH neuronal network is not known. However, a recent pilot study in human patients with Down syndrome (Manfredi-Lozano et al, 2022) who present with both altered learning capabilities and high anxiety shows that pulsatile GnRH therapy restoring the natural pattern of GnRH release improves cognitive performances by 20-30% and that this is accompanied by a decreased functional connectivity in the anxiety-related neuronal network linking the hippocampus to the amygdala to control values (Figueroa-Jimenez, Canete-Masse, et al, 2021;Figueroa-Jimenez, Carbo-Carrete, et al, 2021), as shown by resting-state functional magnetic resonance imaging (fMRI). It would be interesting to determine whether this ventral default mode network linking the hippocampus to the amygdala is also hyperactive in neutered dogs when compared to un-gonadectomized dogs using fMRI.…”
Section: Potential Use Of Pulsatile Gnrh Therapy To Prevent Gonadecto...mentioning
confidence: 99%
“…Of note, bilateral orchidectomy did not affect the rescue of olfaction or recognition memory by pulsatile GnRH, suggesting that the functional improvements observed were independent of the gonadotropic effects of GnRH, and could instead be due to the mobilization of cognitive reserves in male Ts65Dn mice (Manfredi‐Lozano et al, 2022). In a pilot open‐label study of 7 human patients with Down syndrome, pulsatile GnRH therapy using a LutrePulse pump, a safe treatment used for four decades in patients with CHH (Hoffman & Crowley Jr., 1982), for 6 months increased cognitive performances in these patients by 20–30% and restored functional connectivity in neuronal networks known to be altered in Down syndrome (Manfredi‐Lozano et al, 2022), approaching control values using resting‐state functional magnetic resonance imaging (Figueroa‐Jimenez, Canete‐Masse, et al, 2021; Figueroa‐Jimenez, Carbo‐Carrete, et al, 2021; Huang et al, 2015).…”
Section: Rhythmic Gnrh Release Is Required For Olfactory Perception A...mentioning
confidence: 99%